2019
DOI: 10.1111/nuf.12368
|View full text |Cite
|
Sign up to set email alerts
|

Illness acceptance in adolescents: A concept analysis

Abstract: Aim To strengthen the theoretical understanding of illness acceptance in adolescents and to inform healthcare strategies geared toward supporting adolescents with chronic illness. Background Illness acceptance is associated with positive health outcomes. Though well understood in adults with chronic illness, less is known about how this phenomenon ensues in adolescents. Adolescents may have a difficult time accepting an illness due to their unique developmental needs. Consequently, they are vulnerable to poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
(132 reference statements)
1
5
0
2
Order By: Relevance
“…In addition, having an illness appeared to be an additional factor that AYAs had to normalize and integrate into their identity. Consistent with our previous work [26], these additional categories reflect some of the common steps of understanding one's illness, normalizing illness, overcoming limitations, and embracing responsibility that adolescents take in accepting their chronic illness. In addition, learning how to cope is a fundamental aspect of dealing with chronic illness during adolescence [27].…”
Section: Implications For Theorysupporting
confidence: 66%
“…In addition, having an illness appeared to be an additional factor that AYAs had to normalize and integrate into their identity. Consistent with our previous work [26], these additional categories reflect some of the common steps of understanding one's illness, normalizing illness, overcoming limitations, and embracing responsibility that adolescents take in accepting their chronic illness. In addition, learning how to cope is a fundamental aspect of dealing with chronic illness during adolescence [27].…”
Section: Implications For Theorysupporting
confidence: 66%
“…Participants indicated that they were mostly very aware of the difficulties connected to their disease; they described them and the impacts they produced and told how they were adapting their behaviour to new circumstances. The importance of acceptance is well documented in the literature (Ambrosio et al, 2015;Zheng, Bruzzese, & Smaldone, 2019;Richard et al, 2020). These participants developed coping skills by learning what to eat, where they could go, and what activities they could participate in, with support, so that they felt socially safe.…”
Section: Discussionmentioning
confidence: 98%
“…There are four key attributes of illness acceptance in adolescents as described in a conceptual model, which are (a) understanding of illness; (b) overcoming limitations; (c) normalization; and (d) readiness for responsibility (7). Adherence to therapy will continue to increase along with the achievement towards the acceptance stage, which is the highest phase of adherence to therapy (8).…”
Section: Introductionmentioning
confidence: 99%